Grain bran hydrolysates in the production of fruit distillates - Ludmila N. Krikunova; Elena P. Meleshkina; Irina S. Vitol; Elena V. Dubinina; Olga N. Obodeeva (Foods and Raw Materials, 2023)
Currently, there is an urgent need for domestic fermentation activators based on low-cost secondary raw materials. We aimed to study the effect of microbial enzyme preparations with different action on the hydrolysis of proteins and phytin of grain bran to obtain fermentation activators that could become an alternative to imported ones. We studied wheat and rye brans; microbial enzyme preparations with cytolytic, proteolytic, and phytase action; multi-enzyme compositions; and grain bran hydrolysates. Firstly, we determined the kinetic characteristics of enzyme preparations. Secondly, we evaluated their effectiveness in the hydrolysis of the brans. Thirdly, we developed multi-enzyme compositions. Finally, we determined the concentration of soluble forms of phosphorus and free amino acids in the hydrolysates. We determined optimal temperature and pH values for the enzyme preparations. The multi-enzyme compositions contributed to a high accumulation of reducing substances, water-soluble protein, and phosphorus. The concentration of free amino acids in the hydrolysates obtained under the action of the bran’s own enzymes was about 20% higher in the wheat samples, compared to the rye samples. However, when using multi-enzyme compositions in addition to the bran’s own enzymes, the concentration of free amino acids was 1.5 times higher in the rye hydrolysates, compared to the wheat hydrolysates. The use of multi-enzyme compositions under optimal conditions can double the content of phosphorus and free amino acids available for yeast, compared to the control. Our results can be used for further research into using grain bran hydrolysates as an alternative source of nitrogen and phosphorus nutrition for yeast at the fermentation stage of fruit distillate production.